Chronic Hepatitis C Pathogenesis: Immune Response in the Liver Microenvironment and Peripheral Compartment - Rios, Daniela Alejandra; Casciato, Paola Cecilia; Caldirola, María Soledad; Gaillard, María Isabel; Giadans, Cecilia; Ameigeiras, Beatriz; De Matteo, Elena Noemí; Preciado, María Victoria; Valva, Pamela (Frontiers in Cellular and Infection Microbiology, 2021)
Chronic hepatitis C (CHC) pathogenic mechanisms are still a topic of interest, as well as the participation of the immune response in the generation of liver damage. Here, we evaluated immune cell populations and cytokines in liver and peripheral blood (PB) to elucidate their role in CHC pathogenesis. B, CTL, Th, Treg, Th1, Th17 and NK cells localization and frequency were evaluated on liver biopsies by immunohistochemistry, while frequency, differentiation, and functional status on PB by flow cytometry. TNF−α, IL−23, IFN−γ, IL−1β, IL−6, IL−8, IL−17A, IL−21, IL−10 and TGF−β expression were quantified in fresh liver biopsy by RT-qPCR and in plasma by CBA/ELISA. Liver CTL and Th1 at lobular area inversely correlated with viral load (r=−0.469, p=0.003 and r=−0.384, p=0.040). Treg correlated with CTL and Th1 at lobular area (r=0.784, p<0.0001; r=0.436, p=0.013). Th17 correlated with hepatic IL8 (r=0.52, p<0.05) and both were higher in advanced fibrosis cases (Th17 p=0.0312, IL-8 p=0.009). Hepatic cytokines were higher in severe hepatitis cases (IL−1β p=0.026, IL−23 p=0.031, IL−8 p=0.002, TGF−β p=0.037). Peripheral NK (p=0.008) and NK Dim (p=0.018) were diminished while NK Bright (p=0.025) were elevated in patients vs donors. Naïve Th (p=0.011) and CTL (p=0.0007) were decreased, while activated Th (p=0.0007) and CTL (p=0.0003) were increased. IFN−γ production and degranulation activity in NK and CTL were normal. Peripheral cytokines showed an altered profile vs. donors, particularly elevated IL−6 (p=0.008) and TGF−β (p=0.041). Total hepatic CTLs favored damage. Treg could not prevent fibrogenesis triggered by Th17 and IL-8. Peripheral T-lymphocyte differentiation stages shift, elevated cytokines levels and NK-cell count decrease would contribute to global disease.